2014
DOI: 10.4149/neo_2014_054
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of ETS-1, MMP-2 and MMP-9 expression and co-expression in breast cancer patients

Abstract: The aim of this study was to analyse expression of ETS-1 protein and two gelatinases (MMP-2 and MMP-9) and their possible prognostic value in breast carcinoma patients, as well as correlation of their expression with other known prognostic factors such as tumor size, grade, vascular invasion, steroid receptor values, HER2 values and proliferative index. The expression of MMP-2, MMP-9 and ETS-1 was immunohistochemicaly analysed in 121 consecutive primary breast carcinoma patients who underwent surgery at the Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 30 publications
3
27
0
1
Order By: Relevance
“…In addition, the combined effect of these two treatments was stronger than that of single. According to previous reports, MMP-2 and MPP-9 played the important role in the invasion of cancer cells (Fiorentini et al, 2014;Puzovic et al, 2014). In this study, we found that the expression of MMP-2 and MMP-9 were both reduced obviously in the treatment groups.…”
Section: The Invasion Of Pc-3 Cells Was Suppressed By Et-1 Rnai and Esupporting
confidence: 64%
“…In addition, the combined effect of these two treatments was stronger than that of single. According to previous reports, MMP-2 and MPP-9 played the important role in the invasion of cancer cells (Fiorentini et al, 2014;Puzovic et al, 2014). In this study, we found that the expression of MMP-2 and MMP-9 were both reduced obviously in the treatment groups.…”
Section: The Invasion Of Pc-3 Cells Was Suppressed By Et-1 Rnai and Esupporting
confidence: 64%
“…Moreover, MMPs are also linked with inflammation through recruitment of a variety of stromal cells such as fibroblasts and leukocytes [77]. Expectantly, many investigators observed a connection between adverse clinical outcome in breast cancer patients and higher blood levels and/or tumor tissue expression of MMP-2 and MMP-9 [78,79]. Fascinatingly, MMP-9 has been shown to be correlated with the overexpression of poor prognosis marker HER2 [78,80].…”
Section: Adipokine Brief Description In Obesitymentioning
confidence: 98%
“…Повышенная активность ETS1 наблюдалась при РМЖ, РЛ, раке яичников, обо-дочной и прямой кишки и меланоме [33][34][35][36][37]. ETS1 сверхэкспрессируется при инвазивном РМЖ и корре-лирует с его плохим прогнозом [38]. Высокая экспрес-сия ETS1 способствует миграции раковых клеток, инвазии и анкернезависимому росту, в то же время низкая экспрессия ETS1 снижала адгезию клеток HeLa [39].…”
Section: экспериментальные статьиunclassified